Selected aspects of health status of the recently resettled families in Trincomalee - Arulkumaran, S (My University, 2005)
The available information necessary to plan organized health services is scarce. data were collected from randomly selected 404 families by using locally validated interviewer administered questionnaire, anthropometric measurement and focus group discussions. Prevalence of low birth weight and under nutrition among less than five years old children were 25.5 percentage and 43.9 percentage respectively. Worm infection, malaria and diarrhea were common illnesses among them. Health problems detected from adults include, war related injuries, abuse of alcohol, environmental hazards and mental illnesses. Distributions of electricity, toilet facilities and public transport services were very poor in these resettled communities. Communities perceived that primary health care services were not adequate both at domiciliary and institutional levels. Improving expanded programme of immunization, strengthening the capacity of preventive and curative health services, periodic monitoring of health services, further need assessments and provision of occupational opportunities to unemployed, are some of the recommendations made to improve the current situation